A practical approach for the use of high-sensitivity cardiac troponin assays in the evaluation of patients with chest pain - Azar, Rabih R.; Sarkis, Antoine; Giannitsis, Evangelos (The American journal of cardiology, 2021)
Chest pain is a common clinical presentation, especially in the emergency department. Both rapid identification of patients with myocardial infarction as well as those with noncardiac chest pain is important in order to start therapy in the former and avoid unnecessary investigations and delay in discharge in the latter. Beside electrocardiogram, cardiac biomarkers are a key element in decision making. Conventional creatinine kinase and troponin assays are not sensitive enough and have to be repeated at least 6 to 12 hours after initial evaluation. New high-sensitivity cardiac troponin (hs-cTn) tests are currently available and if used appropriately can substantially improve management. Because of their high sensitivity and accuracy, these tests allow measurement of very low serum troponin levels, such as those present in healthy individuals and can detect small changes in troponin concentration within a short time frame. These tests are thus, very useful for the early diagnosis of myocardial infarction but can also be elevated in several other conditions that result in myocardial injury. A good understanding of the analytical characteristics of these assays is of uppermost importance for their appropriate use in clinical practice.
Available online 24 October 2020
Gesehen am 16.02.2022